EVALUATION OF GENOTOXICITY PROFILE OF JASADA BHASMA (A ZINC-BASED MINERAL FORMULATION) IN SWISS ALBINO MICE - BHASKAR, RAVI; Doshi, Megha A; S, Anjana; M, Ravi; Kumar, Naveen; B, Ravi Shankar; Pai, Shakunthala R; Hemalatha, Savitha (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Â Â Objective: Genotoxicity is regarded as one of the potential risk factors for causing pathological diseases. It was confirmed that many chemicals have the mutagenic activity which leads to cancer. A compound which interacts with genetic material DNA and shows adverse effects by altering its structure or function is referred to as genotoxic. Methods: The present study involved 40 Swiss albino mice weighing between 25 and 30 g body weights categorized into four different groups. Group-I (normal control) received 0.5% carboxymethyl cellulose as vehicle. Group-II (toxicant control) received 40 mg/kg/body weight cyclophosphamide on the 28th day. Group-III and IV received test drug JB 15.6 mg/kg and 78 mg/kg, respectively, for 28 consecutive days. Blood samples were collected and processed for evaluating by comet assay. The animals were sacrificed and collected the bone marrow from both the femur for chromosomal aberration and micronuclei assay. Results: JB administered at two different dose levels did not show any significant changes in the comet assay parameters, no micronucleus was found and did not produce any chromosomal aberrations both numerically and structurally when compared to positive test control group. Conclusion: The genotoxicity evaluation of JB did not show any chromosomal aberrations and presence of micronucleus. Thus, the safety data will refine therapeutic utility of JB encouraging their rationale use and translate into greater and broader utilization of JB.